The effect of thriving at work on work-family conflict: the mediating role of workaholism - Ni, Xudong; Zeng, Zining; Zhou, Jinyu (Frontiers in Psychology, 2023)
Thriving at work is a relatively new concept in the field of organizational behavior, and many scholars have emphasized the importance of its outcomes in the last decade or so, but we still know little about the possible dark side of thriving at work. In this study, based on the conservation of resources theory, we studied the effect of thriving at work on work-family conflict, the mediating effects of workaholism, and the moderating effects of work-family separation preference and trust climate. By analyzing 372 samples, we found that thriving at work was significantly and positively related to work-family conflict; workaholism partially mediated the relationship between thriving at work and work-family conflict; work-family separation preference negatively moderated the relationship between thriving at work and workaholism. The moderating role of the trust climate was not verified. This paper explores the internal mechanisms by which thriving at work negatively affects the family sphere and helps individuals avoid falling into the dark side of thriving at work.